2019
DOI: 10.1002/hbm.24537
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion weighted imaging using combined gradient/spin echo EPIK: Brain tumour applications in hybrid MR‐PET

Abstract: Advanced perfusion‐weighted imaging (PWI) methods that combine gradient echo (GE) and spin echo (SE) data are important tools for the study of brain tumours. In PWI, single‐shot, EPI‐based methods have been widely used due to their relatively high imaging speed. However, when used with increasing spatial resolution, single‐shot EPI methods often show limitations in whole‐brain coverage for multi‐contrast applications. To overcome this limitation, this work employs a new version of EPI with keyhole (EPIK) to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…In this work, the phase correction method [41,42] was applied to the functional data sets to partially minimise the influence of large cerebral vessels. In an earlier work, a spin-echo version of EPIK was also verified for the detection of haemodynamic signals in perfusion studies [37]. This suggests that a spin-echo configuration can be systematically transferred to TR-external, gradient-echo EPIK and the same high-resolution advantage obtained in this work can also be expected in its spin-echo version, resulting in increased spatial specificity to aid the detection of neural activity.…”
Section: Non-bold Contrastssupporting
confidence: 66%
See 1 more Smart Citation
“…In this work, the phase correction method [41,42] was applied to the functional data sets to partially minimise the influence of large cerebral vessels. In an earlier work, a spin-echo version of EPIK was also verified for the detection of haemodynamic signals in perfusion studies [37]. This suggests that a spin-echo configuration can be systematically transferred to TR-external, gradient-echo EPIK and the same high-resolution advantage obtained in this work can also be expected in its spin-echo version, resulting in increased spatial specificity to aid the detection of neural activity.…”
Section: Non-bold Contrastssupporting
confidence: 66%
“…This work presents a novel fMRI methodology, providing a half-millimetre in-plane resolution with whole-brain coverage. The imaging method was developed based on the combination of TR-external EPI phase correction [26,27] with EPI with keyhole (EPIK) [28][29][30][31][32][33][34][35][36][37][38][39], both of which have been shown to be effective in improving the spatial resolution and brain coverage while maintaining comparable BOLD detection performance when compared to a standard EPI method [27,32,[34][35][36][37]. The developed imaging method is termed "TR-external EPIK" [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we applied TR-external EPIK, to identify the laminar signals from most of the cerebral cortex with a 0.63 mm iso-voxel size in healthy volunteers. It has been previously shown that EPIK [45][46][47][48][49][50] can offer higher spatial resolution in dynamic MR studies with comparable hemodynamic-response detection compared to routine EPI [51][52][53][54][55]. Moreover, the combination of TR-external phase correction with EPIK has been shown to offer a further enhancement of the spatial resolution [49,56].…”
Section: Introductionmentioning
confidence: 99%
“…This acquisition scheme can achieve a higher apparent temporal resolution than the community‐standard method, EPI. This work employs 48 central k ‐space lines for the keyhole region (Shah et al, 2019 ; Yun et al, 2013 , 2020 ; Yun & Shah, 2017 , 2019 ; Zaitsev et al, 2001 ). A more detailed description of the features of EPIK is given in Supporting Information (see 5.1. with Figure S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…This work presents a novel fMRI methodology, providing a half‐millimetre in‐plane resolution with whole‐cerebrum coverage. The imaging method was developed based on the combination of ‘TR‐external EPI phase correction’ (Wielopolski et al, 1998 ; Yun & Shah, 2020 ) with ‘EPI with keyhole’ (EPIK) (Caldeira et al, 2019 ; Shah, 2015 ; Shah et al, 2019 ; Shah & Zilles, 2003 , 2004 ; Yun et al, 2013 , Yun & Shah, 2019 , Yun & Weidner, 2019, 2020 ; Yun & Shah, 2017 , 2019 ; Zaitsev et al, 2001 , 2005 ), both of which have been shown to be effective in improving the spatial resolution and brain coverage while maintaining comparable BOLD detection performance when compared to a standard EPI method (Caldeira et al, 2019 ; Shah et al, 2019 ; Yun et al, 2013 ; Yun & Shah, 2017 , 2019 , 2020 ). The developed imaging method is termed ‘TR‐external EPIK’ (Yun et al, 2020 ; Yun & Shah, 2019 ).…”
Section: Introductionmentioning
confidence: 99%